Digital communication strategy of Instagram @chinese_server in deconstructing anti-Chinese sentiment - Obed Adi Nugroho; Sri Hastjarjo; Yosia Enggar Kurniawan (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2025)
To date, negative sentiments toward the Chinese ethnic group in Indonesia still exist. Using a content analysis research design, this study attempts to analyze the effective communication strategies of the Instagram account @chinese_server in rectifying various negative sentiments toward the Chinese ethnic group. The results show that the account effectively deconstructs negative sentiments towards the Chinese ethnicity, including pro-PRC, exclusivity, non-nationalism, and atheism, through historical and social narratives packaged in short videos. The account can reach cross-ethnic audiences, encourage multicultural understanding, and facilitate a shift in attitude from ethnocentrism to ethnorelativism. However, resistance is still evident in the form of negative comments. This study is expected to contribute to the discourse on the role of social media in shaping public perception and multicultural education.